In vitro evaluation of anthelmintic activity of tannin-containing plant Artemisia extracts against Haemonchus contortus from goat: Anthelmintic activity of tannin-containing plants Artemisia (Journal of the Bangladesh Agricultural University, 2019)
Gastrointestinal nematode causes significant production losses in grazing ruminants and anthelmintic resistance are increasing at an alarming rate. The aim of this study was to evaluate the in vitro anthelmintic effects of tannin-containing plant Artemisia vulgaris against stomach worm Haemonchus contortus of goat. In this respect, in vitro anthelmintic activities of crude aqueous and ethanolic extracts of aerial parts of A. vulgaris were investigated on eggs, larvae (L3) and adults of H. contortus in the laboratory. Experimental plant Artemisia was collected, dried in shade and grinded to coarse powder and subjected to prepare crude aqueous and ethanolic extract. The experiment revealed that crude ethanolic extracts completely inhibited egg hatching at concentration of 5 mg/ml whereas aqueous extracts at concentration of 10 mg/ml. After exposure of 8 hours, the crude ethanolic extracts inhibited 69.33%, 51% and 38% larval motility tested at 20 mg/ml, 10 mg/ml and 5 mg/ml concentrations, respectively while the crude aqueousextracts inhibited 57.33%, 48.67% and 34.67% at the same concentrations. The ethanolic extract showed better in vitro effects against adult stomach worm than the aqueous extract in terms of motility inhibition at different hours post-treatment. Dose dependent effects were also observed for both extract. After 2 and 8 hours of exposure, the ethanolic extract induced 53.33% and 100% mortality at the highest tested concentration respectively, while the aqueous extract induced 47.67% and 86.67% at the same concentration. To our best knowledge, this is the first study in Bangladesh on the in vitro anthelmintic effects of A. vulgaris against H. contortus. Further in vitro and in vivo trials with this plant are required to evaluate their anthelmintic effects precisely.J Bangladesh Agril Univ 17(3): 363–368, 2019